Potential impacts of climate change and land-use change on hydrological drought in the Western Cape (South Africa) - Naik, Myra (Department of Environmental and Geographical Science, 2023)
The Western Cape (South Africa) recently witnessed the most severe drought on record. The meteorological drought, which was characterised by below-normal rainfall for three consecutive years (2015 – 2017), cascaded to agricultural and then hydrological drought, resulting in devastating socio-economic consequences. While some studies indicate that climate change may increase the severity and frequency of droughts in the Western Cape in the future, there is a lack of information on how to mitigate the effects of future climate change on hydrological drought. This dissertation therefore investigated the extent to which land-use changes could be applied to reduce climate change impacts on future hydrological drought in this region. For the study, the revised Soil Water Assessment Tool (SWAT+) was calibrated and evaluated over four river basins in the Western Cape, and the climate simulation dataset from the COordinated Regional Downscaling EXperiment (CORDEX) was bias-corrected. Using the bias-corrected climate data as a forcing, the SWAT+ was used to project the impacts of future climate change on water yield and hydrological drought in the four basins and to quantify the sensitivity of the projection to four feasible land-use change scenarios in these basins. The relevant land-use scenarios are the expansion of mixed forests (FrLand), the restoration of grassland (GrLand), the restoration of shrubland (SrLand), and the expansion of cropland (CrLand). The model evaluation shows good agreement between the simulated and observed monthly streamflow at hydrological stations, and the bias correction of the CORDEX datasets improved the quality of the SWAT+ hydrological simulations in the four basins. The climate change projection depicts an increase in temperature and potential evapotranspiration but a decrease in precipitation and all the hydrological variables. Drying is projected across the Western Cape, and the magnitude of such drying increases with higher global warming levels (GWLs). The land-use changes alter the impacts of climate change by influencing the hydrological balance. While FrLand mitigates the impacts of climate change on the frequency of hydrological drought by increasing streamflow, soil water and percolation, CrLand mitigates the impacts by increasing surface runoff. However, the magnitudes of these land-use change impacts are very small compared to the climate change impacts. Hence, the results suggest that land-use changes may not be an efficient strategy for mitigating the climate change impacts on hydrological drought over the region. The findings obtained from this 2 research provide relevant information towards mitigating the severity of future droughts and improving water security in Western Cape River Basins.